A Major Subset of Mutated CLL Expresses Affinity-selected and Functionally Proficient Rheumatoid Factors. Issue 4 (23rd April 2021) - Janssen, Jerry; Donner, Naomi; Li, Zhen; Wormhoudt, Thera A.M.; Wagner, Koen; Guikema, Jeroen E.J.; van der Schoot, C. Ellen; Kater, Arnon P.; Feizi, Ten; Bende, Richard J.; van Noesel, Carel J.M.
Abstract : Supplemental Digital Content is available in the text.